Revision surgery for malocclusion after open reduction of mandibular fracture: a case report - Watanabe, Takuma; Hirota, Makoto (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2025)
Insufficient treatment of mandibular fractures can result in malocclusion, often necessitating revision surgery. Therefore, appropriate surgical treatment by oral and maxillofacial surgeons with adequate consideration of the occlusion is crucial. Moreover, in patients with bone defects between the fractured ends, bone grafting may be required. A 48-year-old man was referred to our department with malocclusion after initial surgery for mandibular fracture performed by plastic surgeons at another hospital. We performed revision surgery with bone grafting for a bone defect, and favorable postoperative occlusion and bone healing were achieved. Occlusal reconstruction is paramount, and bone grafting may be required if the procedure creates a bone defect. The skills and technique of oral and maxillofacial surgeons are critical, although collaboration with plastic surgeons may be necessary.